Interpretation of surface degradation on polymeric insulators. (January 2019) - Verma, Alok Ranjan; Subba Reddy, B.
Abstract: Silicone rubber based polymeric insulators are being used widely used as outdoor insulation for high voltage applications. However, their long-term service life performance is highly dependent on local environmental conditions that cause deterioration of material properties of the insulators. In the present work, tracking and erosion studies are conducted on silicone rubber samples using. Inclined Plane Tracking (IPT) and Erosion method based on IEC 60587. The contaminants used to simulate different environmental conditions are as per standard and in addition acidic rain composition is used. Leakage current flowing through samples was continuously monitored and recorded over the experimental duration. The consequence of leakage current variation is analyzed using. Recurrent Plot (RP) Analysis and this resulted in variation of quantitative parameters Recurrence Rate (RR), Determinism (DET), Entropy (ENT) and Length (L) these are used to interpret the tracking and erosion performance of silicone rubber samples. Further, physico-chemical analysis is conducted using Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDAX) and Fourier Transform Infra-Red (FTIR) spectroscopy to observe surface morphology and chemical changes happened in the samples. Thermo-Gravimetric Analysis (TGA) is performed to observe thermal stability and presence of Aluminum Tri-hydrate (ATH) fillers before and after experiments. The investigations show RP method as a potential tool for detection and diagnostic of polymeric insulators. Highlights: Investigations on tracking and erosion on polymeric insulators under AC stress is attempted Leakage current monitored regularly for entire experimental duration Significance of leakage current is analyzed using Recurrence plot analysis Surface morphological changes on polymer insulators conducted Investigations reveal material degradation, depolymerization and loss of ATH.